2019
DOI: 10.3390/ma12060902
|View full text |Cite
|
Sign up to set email alerts
|

Method of Optimisation for Ambient Temperature Cured Sustainable Geopolymers for 3D Printing Construction Applications

Abstract: Since the initial introduction of geopolymers, these materials have been characterised as environmentally-friendly sustainable substitutes for ordinary Portland cement (OPC). There is a routine increase in the application of geopolymers, especially in advanced technologies. Because of its better rheological characteristics compared to OPC, geopolymers are appropriate materials for extrusion-based 3D printing technologies. This paper focuses on the optimisation of an ambient temperature cured geopolymer for 3D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 36 publications
2
60
1
Order By: Relevance
“…It should be noted that the observed significantly higher inter-layer bond strength in the printed UHPFRC composite as compared to that of the printed UHPFRC matrix shall be investigated comprehensively in our future research. The inter-layer bond strength of the UHPFRC observed in this study is significantly higher than the values reported in the literature for normal strength concrete [35], geopolymer concrete [8,36], fiber- reinforced concrete [12], fiber-reinforced geopolymer concrete [13] due to the superior mechanical properties of the UHPFRC. Figure 19 shows the apparent porosities of the UHPFRC matrix and composite.…”
Section: Figure 16 Flexural Toughness Of Uhpfrc Matrix and Compositescontrasting
confidence: 86%
See 3 more Smart Citations
“…It should be noted that the observed significantly higher inter-layer bond strength in the printed UHPFRC composite as compared to that of the printed UHPFRC matrix shall be investigated comprehensively in our future research. The inter-layer bond strength of the UHPFRC observed in this study is significantly higher than the values reported in the literature for normal strength concrete [35], geopolymer concrete [8,36], fiber- reinforced concrete [12], fiber-reinforced geopolymer concrete [13] due to the superior mechanical properties of the UHPFRC. Figure 19 shows the apparent porosities of the UHPFRC matrix and composite.…”
Section: Figure 16 Flexural Toughness Of Uhpfrc Matrix and Compositescontrasting
confidence: 86%
“…including printing configurations and printing materials [30]. Similar anisotropic behavior has been reported in the literature for normal strength concrete [7], high performance concrete [12] and geopolymers [8,13].…”
Section: Fresh Propertiessupporting
confidence: 81%
See 2 more Smart Citations
“…The AFGC guide summarizes the different methods available for determining durability indicators as shown in Table 1. Example of research projects on tensile strength of 3D printed materials for construction [22][23][24]. The concept of printability was also investigated in literature research, and linked to some indicators, such as the shear rate, viscosity, and thixotropy [6,25].…”
Section: Durability Indicatorsmentioning
confidence: 99%